The Water-Energy-Food Nexus Index for Bulgaria – Overview and Comments - Hristova, Nelly; Nikolova, Nina; Stoyanova, Elitsa (Geographica Pannonica, 2024)
The 'Water–Energy–Food' (WEF) Nexus concept is evolving and expanding, as it is essential for finding synergies and compromises between these three sectors under climate change and for building a green economy. This work aims to present and analyse some indicators of the WEF Nexus Index for Bulgaria, according to which the country ranked 66th in the world in 2022. The data sources were the publications of the National Statistical Institute, the Ministry of Environment and Water, etc. The current study found that most indicators in the three pillars objectively assess the country's water resources, energy, and food sectors. The findings reveal a lack of information about the 'Food' pillar, resulting in an inability to assess this pillar objectively. Additionally, the evaluation of several sub-pillars based on the official data shows inaccuracies in the final WEF Index result for the country. This work represents the first presentation of the WEF Nexus Index for Bulgaria and continues the authors' study on the dynamics of the water, energy, and food sectors.
Keywords: Water–Energy–Food (WEF); WEF Nexus Index; Bulgaria